Identifying Biophilic Design Elements in Streetscapes: A study of visual attention and sense of place - Milliken, Peter. (Tufts University. Tisch Library., 2019)
This thesis is an examination of the role of biophilic elements in streetscapes. Literature was reviewed to gain an understanding of how people react to interacting with nature in various forms and settings. Research was done on streetscapes regarding planning and design after learning about the human-nature interaction in place-making. Questions regarding what biophilic elements are present in streetscape designs, how these designs affect people, and how these elements can be introduced in future plans arose. From here, methods were established using 3M's Visual Attention Software (VAS) eye-tracking emulation software to show where an observer may instinctually focus when presented with a point of view within streetscapes samples of the regional development of Devens, Massachusetts. After figuring out how biophilic elements increase concentration and focus within locations along the streetscape, acknowledgement of the implications of this study are made for future planning and policy practitioners.; Thesis (M.A.)--Tufts University, 2019.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Justin Hollander.; Committee: Mark Chase.; Keywords: Urban planning, and Design.